2020
DOI: 10.1002/adfm.202007277
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbiturils‐Mediated Noble Metal Nanoparticles for Applications in Sensing, SERS, Theranostics, and Catalysis

Abstract: Noble metal nanoparticles (NMNPs), which spring up like mushrooms, are gaining momentum owing to their unique physicochemical characteristics. Cucurbiturils, a class of synthetic macrocycles with intriguing and peculiar host–guest properties, have stimulated tremendous research interest in recent years. The marriage of NMNPs with cucurbiturils is expected to integrate and enhance the excellent characteristics of both components, e.g., precisely controlled particle size, stability, assembly, surface functionali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(73 citation statements)
references
References 238 publications
0
66
0
Order By: Relevance
“…[259][260][261] More specifically, the macromolecules capture and place the analyte molecules within the enhancing surface plasmon through weak intermolecular interactions, such as cation-dipole interactions or hydrophobic force. 262 Therefore, this approach is most useful for SERS analysis of analyte molecules with a decent Raman cross-section but low affinity to the enhancing surface. For example, Pérez-Juste, Pastoriza-Santos, et al designed reusable supramolecular plasmonic films composed of multiple layers of plasmonic Au nanospheres, which have been modified with ammonium pillar [5] arene (AP[5]A) macrocycles for the detection of polyaromatic hydrocarbons, as illustrated in Figure 19C.…”
Section: Reversible Intermolecular Interactionsmentioning
confidence: 99%
“…[259][260][261] More specifically, the macromolecules capture and place the analyte molecules within the enhancing surface plasmon through weak intermolecular interactions, such as cation-dipole interactions or hydrophobic force. 262 Therefore, this approach is most useful for SERS analysis of analyte molecules with a decent Raman cross-section but low affinity to the enhancing surface. For example, Pérez-Juste, Pastoriza-Santos, et al designed reusable supramolecular plasmonic films composed of multiple layers of plasmonic Au nanospheres, which have been modified with ammonium pillar [5] arene (AP[5]A) macrocycles for the detection of polyaromatic hydrocarbons, as illustrated in Figure 19C.…”
Section: Reversible Intermolecular Interactionsmentioning
confidence: 99%
“…Owing to the strong hydrophobic interactions of CB[n], they are appropriate candidates to form the inclusion complex between the doped molecules for the preparation of host-guest RTP materials. [133][134][135] Additionally, the RTP properties of CB-based material systems can be effectively modulated by tuning ion-dipole interactions between carbonyl oxygens of glycoluril and positively charged atoms of dopants. The CB[n] (n = 7 or 8) induced host-guest RTP (CB-RTP) materials were reported firstly by Tao and co-workers [136] in 2007 using quinoline derivatives as luminophores; by tuning the luminescent guest of quinoline derivatives (Scheme 2, G14-G19), the RTP emission bands could be tuned from 498 to 530 nm.…”
Section: Macrocyclic Molecule Matrixmentioning
confidence: 99%
“…Host–guest chemistry offers a reversible and versatile way to achieve high-fidelity recognition between host and guest molecules; therefore, it is widely employed in homogeneous solutions 1 4 . In recent studies, host–guest systems have been used on solid surfaces to functionalize nanomaterials 5 12 . The results showed that the host–guest complexation behavior on surfaces may differ from those observed in solutions.…”
Section: Introductionmentioning
confidence: 99%